Predictors of COVID-19 Vaccine Hesitancy and Its Relation to the Educational Background in Pakistan - Muhammad Daniyal Munir; Hamza Afzaal; Muhammad Hamdan Sajjid; Saiqa Anwar; Muhammad Hassan Shabbir (Universitas Pendidikan Indonesia (UPI), 2021)
We identify groups most at risk of ambiguity and reluctance to take a COVID-19 vaccination in a large sample of Pakistani people. A descriptive cross-sectional study was conducted to poll the Pakistani population on their views regarding COVID-19 vaccinations acceptance. COVID-19 vaccination acceptance among the general public in Pakistan was poor 37.8%. Multivariate analysis showed that participants who had received their Influenza vaccination in recent years are more likely to show their interest in COVID-19 vaccination acceptance. A similar pattern emerged among individuals who thought vaccinations are usually safe and showed their willingness to pay for vaccines. In contrast, individuals over 45, and those unemployed, were less likely to accept the COVID-19 vaccine. Adopting COVID-19 vaccinations was also less probable among individuals who thought there was a conspiracy behind them. Public health officials must take systematic steps to decrease vaccination apprehension and increase vaccine uptake. They should be concerned about the low rate of acceptance and the need for additional research into the underlying reasons and awareness efforts. These measures should include restoring public confidence in national health authorities and organized awareness efforts that provide clear information regarding vaccination safety, effectiveness, and manufacturing.